Analysis of Conformity Between Expectations and Realization in Sharia Bank' Financial Services in Aceh Tamiang District - Noviana, Nova; Fuad, Muhammad; Setianingsih, Dias (Fin Sinergy: Jurnal Manajemen Keuangan, 2023)
This research aims to determine the correspondence between expectations and realization in financial services based on the dimensions of services provided at Sharia Commercial Banks and this research was specifically carried out at Bank Syariah Indonesia Kualasimpang City Branch Office. The data used is primary data sourced from 100 research respondents at Bank Syariah Indonesia Kualasimpang City Branch Office. The data analysis method uses quantitative methods with difference test analysis and Cartesian diagrams. The research results showed that there was a difference between expectations or in this case the customer's expectations and the realization or in this case the performance of the Indonesian Syariah Bank Kualasimpang City Branch Office with a value of 405,000>403.4211. Based on the Cartesian diagram, it is known that the customer's expectations and the bank's realization (performance) are in quadrant III and quadrant IV. In quadrant III, it can be seen that it contains factors that are considered less important by customers and in fact their performance is not very special. Then in quadrant II, there are factors that are considered important by customers and are in accordance with what they feel so that the level of satisfaction is relatively higher. Therefore, the attributes included in this quadrant must be maintained.